Open clusters: I. Fundamental parameters of B stars in NGC 3766 and NGC 4755 - Aidelman, Yael Judith (2012)
Context. Spectroscopic investigations of galactic open clusters are scarce and limited to a reduced sample of cluster members. Aims. We intend to perform a complete study of the physical parameters of two galactic clusters as well as of their individual members. Methods. To carry out this study, we used the BCD (Barbier-Chalonge-Divan) spectrophotometric system, which is based on the study of the Balmer discontinuity and is independent of interstellar and circumstellar extinction. Additional physical properties were derived from the line profiles (FWHM) and stellar evolution models. We analyzed low-resolution spectra around the Balmer discontinuity for normal B-type and Be stars in two open clusters: NGC 3766 and NGC 4755. We determined the stellar fundamental parameters, such as effective temperatures, surface gravities, spectral types, luminosity classes, absolute and bolometric magnitudes, and color gradient excesses. The stellar rotation velocity was also determined. Complementary information, mainly stellar mass, age, and radius of the star population were calculated using stellar evolution models. In some cases, the stellar fundamental parameters were derived for the first time. The obtained results allowed us also to determine the reddening, age, and distance to the clusters. Results. The cluster parameters obtained through the BCD method agree very well with those derived from classical methods based on photometric data. The BCD system also provides physical properties of the star members. This study enables us to test the good behavior of M bol(λ 1,D)-calibrations and detect systematic discrepancies between log g estimates from model atmospheres and those derived from stellar evolution models. To improve our knowledge on the formation and evolution of the clusters, more statistical studies on the initial mass luminosity and angular momentum distributions should be addressed. Therefore, the BCD spectrophotometric system could be a powerful tool for studying far galactic and extragalactic clusters with the generation of large telescopes and the multi-object technique. © 2012 ESO.